Tofu Wastewater Treatment with Variation of Air Rate in Aeration Suspension System (Nusantara Science and Technology Proceedings, 2021)
There are many small-scale industries in Indonesia. It is also rare to find a tofu industry that has wastewater treatment. This contributes to water pollution and worsens river water quality if it is not treated first. This study aims to treat small-scale tofu industrial wastewater easily to reduce its organic content with a suspension aeration system. Modified seeding process with the addition of a small amount of Calcium Carbonate to raise the pH. The seeding process was carried out for 20 days with the highest MLSS value of 1136 mg/L. Furthermore, the acclimatization process was carried out for 11 days for reactor stability with a COD removal percentage of 83.15%. The running process was carried out in an aeration tank for 18 hours and continued with the best recirculation at 5 hours with an oxygen rate of 12 L/min. The best achievement in decreasing COD content was 89.79%, TSS was 74.14% and N-Total was 69.55%.